Designing of multiple deferred state sampling plan for generalized inverted exponential distribution. Issue 1 (2nd January 2017) - Balamurali, Saminathan; Jeyadurga, P.; Usha, Mahalingam
ABSTRACT: In this article, we propose a sampling plan called a multiple deferred state sampling plan for sentencing a lot based on the information of current and successive lot samples. Based on this sampling plan, the median life of the product is assured based on a time-truncated life test where the lifetime of the product follows the generalized inverted exponential distribution. The quality of the product is measured by its median life. The optimal parameters of the proposed plan are obtained by using the approach of two points on the operating characteristic curve. Tables are also constructed for determining the optimal parameters with various shape parameters. The implementation of the proposed plan is illustrated with examples. The performance of the proposed plan is compared with the performance of existing sampling plans under the generalized inverted exponential distribution.